EFEKTIVITAS PROGRAM PASCA-SEKOLAH BAGI KEMANDIRIAN PENYANDANG DISABILITAS INTELEKTUAL - Mumpuniarti Mumpuniarti; Tin Suharmini; Praptiningrum Praptiningrum (Department of Special Education, 2014)
The purpose of reseach is to describe of post-school’s program for developing independence of intellectual disabilities effectively; the opinion’s teacher about the post-school’s program for intellectual disabilities; as soon as the support’s usefulness resources can be used for implementation of post-school’s program. The research method is to conduct a survey through opened questionnaire and interview for teachers, and data analysis is to conduct with category base on aspect of need’s post-schools program. Result of the study is to point out as: the efectiveness of post-school’s program is orientated to trend of take action against for the skill has beenlearned in the moment intellectual disabilitas at the yunior high schools stage; the opinion of teacher is only skill to be rely on efective for pasca-schools program;as soon as the support’s resources for usefullness to the limit of that competen to exertion of schools.Penelitian bertujuan mendeskripsikan program-program yang berorientasi ditindaklanjuti pasca-sekolah yang secara efektif berfungsi meningkatkan kemandirian penyandang disabilitas intelektual; pandangan guru tentang program pasca-sekolah bagi disabilitas intelektual; serta sumber daya pendukung yang dapat digunakan keterlaksanaan program pasca-sekolah. Metode penelitian dilaksanakan dengan survey instrumennya adalah angket terbuka dan wawancara kepada guru, serta analisis dilaksanakan secara kategoris berdasarkan aspek-aspek kebutuhan program pasca-sekolah. Hasil penelitian menunjukkan bahwa keefektifan program cenderung berorientasi menindaklanjuti keterampilan yang telah dilatihkan pada saat siswa disabilitas intelektual berada di sekolah menengah; pandangan para guru hanya keterampilan yang menjadi andalan efektif untuk pasca-sekolah; serta sumber daya pendukung yang digunakan sebatas kemampuan sekolah.